P05.03 Stereotactic Radiosurgery to Surgical Cavity Post Resection of Brain Metastases: Local Recurrence and Overall Survival Rates. A Single Centre Experience. (19th September 2018) - Higgins, M J; Burke, O; Nugent, K; Skourou, C; Dunne, M; Javadpour, M; Fitzpatrick, D; Faul, C
Abstract: Background: We reviewed local control (LC) and overall survival (OS) post intracranial SRS to cavity post resection of brain metastases at one institution, and factors affecting LC. Material and Methods: A retrospective review was conducted of adjuvant SRS at one institution from 2013 to 2016. Patient records, treatment plans, and diagnostic images were reviewed. Local failure was MRI defined. Categorical variables were analysed using chi-square and Fisher's exact tests. Continuous variables were analysed using Mann-Whitney tests. The Kaplan-Meier method was used to estimate survival times and the log-rank test was used to compare differences in survival. Results: 47 patients with 48 cavities were treated with SRS post operatively. LC rate was 69%, and the distant intracranial failure rate was 47%. The 12 month freedom from local recurrence (FFLR) was 77% (63–91%). Median OS (95% CI) was 22.7 (14.6–30.8) months. Patients with a single metastasis had longer FFLR (30.1 vs 14.4 months; p = .014). Median interval from surgery to SRS was 6.3 weeks. Patients with interval > 7 weeks had increased local recurrence (LR) (62%) than < 7 weeks (37%), p = 0.025.Patients with a margin < 2mm were more likely to experience LR (48%) than those with margin equal to 2mm (20%); this approached statistical significance (p = 0.063). The median follow up for all patients was 15.4 months (2–41). Conclusion: We determined LC and OS using adjuvant SRS at our institution. Based on the findings of this retrospective review SRS should be given promptly post operatively with a 2mm PTV margin.